SYNTHESIS AND CHARACTERIZATION SYSTEM CaO-MgO - Garrido Schaeffer, A. (1998)
In the present work are synthesized a series of oxides of the system of MgO/CaO, with different proportions in the cations, by the method of coprecipitation of Rao on carbonates precursors and their subsequent calcination to 1173 ºK. The carbonates precursors as the final oxides were analyzed by X Ray Fluorescence, Atomic Absorption and Neutronic Activation. The identification of the different crystalline phases are realized by X-rays Difraction and the presence of adsorbates carbonates species by Fourier Transformed lnfrared Spectroscopy.